Sensitivity of an intense rain event between atmosphere‐only and atmosphere–ocean regional coupled models: 19 September 1996. (12th April 2014) - Berthou, Ségolène; Mailler, Sylvain; Drobinski, Philippe; Arsouze, Thomas; Bastin, Sophie; Béranger, Karine; Lebeaupin‐Brossier, Cindy
<x xml:space="preserve">Abstract</x> The representation of Mediterranean intense rain events in regional coupled models is of great importance for impact studies of climate change. It is investigated through the comparison of an atmosphere‐only simulation forced by a coarse‐resolution sea‐surface temperature (SST), an atmosphere–ocean coupled simulation generating a high‐resolution SST and an atmosphere‐only simulation forced by a high‐resolution monthly smoothed SST. The Cévennes, located in Southern France, is a region of high interest because of its frequent intense rain events and the proximity of the Gulf of Lion, where intense air–sea exchanges happen during mistral and tramontane wind bursts. Focus is given to one of the most intense rain events of the 20 year simulations (1989–2009): 19 September 1996, for which the change in the rain location between the atmosphere–ocean simulation and the atmosphere‐only simulation forced by the coarse‐resolution SST is large. In this case, the change in the rain location can be attributed mainly to a long‐term change in the SST of 1.5 K, with a smaller but significant contribution of submonthly coupled effects such as cooling of the SST in the Gulf of Lion after moderate mistral events that occurred before the precipitation event. The change in the location of precipitation is related to a wind change of 5ms−1. This wind deviation originated from the combined effects of a surface pressure anomaly, stronger stratification on the western side of the coastal front in the Gulf of Lion and the enhanced blocking effect of the Alps.